Anatomy of an aerobic workout - Pyne, D. (2001)
Designing effective training sets is a daily responsibility for swimming coaches. Irrespective of the level of the group or of individual swimmers, training must be well planned and specific for the needs and abilities of the swimmers. Workouts are generally planned in advance, but may need modifying depending on the readiness and/or fatigue levels of the swimmers at the time of training. The following workout is classified as a moderate intensity aerobic workout of 6,500 m that encompasses several features of interest. This workout would be suitable for a well-trained group of age group or senior level swimmers. Younger or less skilled swimmers may need to reduce the number and length of efforts and increase the cycle (work:rest ratio) times.